2005
DOI: 10.1111/j.1540-8159.2005.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Cooled‐Tip and 8‐mm‐Tip Catheters for Radiofrequency Catheter Ablation of the Cavotricuspid Isthmus: A Meta‐Analysis

Abstract: The present meta-analysis confirms that cooled-tip and large-tip catheters are equally efficient for cavotricuspid isthmus ablation with both similar primary success rates and procedure parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…Conventional ablation technique requires creation of a complete line of conduction block (“pullback” ablation) across CTI, from the tricuspid valve to the inferior vena cava. This approach has a high overall success rate but results in variable, sometimes lengthy procedure times, mainly due to anatomic variation 2–5 . The recently proposed “maximum voltage‐guided” (MVG) ablation technique targets high‐voltage isthmus electrograms to ablate the functionally important anatomic muscle bundles alone, without drawing a complete anatomic line 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ablation technique requires creation of a complete line of conduction block (“pullback” ablation) across CTI, from the tricuspid valve to the inferior vena cava. This approach has a high overall success rate but results in variable, sometimes lengthy procedure times, mainly due to anatomic variation 2–5 . The recently proposed “maximum voltage‐guided” (MVG) ablation technique targets high‐voltage isthmus electrograms to ablate the functionally important anatomic muscle bundles alone, without drawing a complete anatomic line 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Feld et al performed catheter ablation of type 1 atrial flutter using large‐tip electrode catheters in 169 patients and demonstrated that acute success rate is 93% and 97% patients had no recurrence of atrial flutter 18 . Furthermore, a meta‐analysis study confirmed that cooled‐tip and 8‐mm large‐tip catheters are equally efficient for CTI ablation with both similar primary success rates and procedure parameters 19 . Cryoablation of the CTI, as compared with radiofrequency ablation, produced significantly less pain during application of the energy.…”
Section: Outcome Of Radiofrequency Ablationmentioning
confidence: 99%
“…A metaanalysis by Da Costa et al . [24] which included seven trials and 603 patients concluded that irrigated-tip and 8-mm-tip catheters are equally effective for isthmus ablation with similar success rates (84% vs.85%) and procedural characteristics (RFA time, fluoroscopy and total procedure time). “In the review article by Da Costa et al ., the authors concluded that 8-mm tip catheters seem to be more effective in patients with straight isthmus morphology and irrigated catheters appear to be more effective in cases of complex CTI anatomy” [25].…”
Section: Tools Facilitating Rfa Of the Ctimentioning
confidence: 99%
“…“This method has been accepted as a first-line therapeutic option in the treatment of CTI-dependent Afl and one of the most commonly performed procedures in electrophysiology” [5, 6]. RFA of CTI-dependent Afl is a highly successful intervention, but in about 1–12% of the patients the RFA remains unsuccessful [7-10]”. The principal obstacle to successful ablation is the complex and variable anatomy of the CTI which has been demonstrated in anatomical and angiographic studies” [5, 6].…”
Section: Introductionmentioning
confidence: 99%